“Finding happiness in daily work”: an ecological study on the emotions of novice EFL teachers in rural primary schools in China - Yao, Yujing; Xu, Jie; Yan, Conggen (Frontiers in Psychology, 2023)
While research on teacher emotions has grown in the past decades, little is known about rural teachers' and novice teachers' emotions. Based on ecological theory, this study selected two novice EFL teachers as the research objects. The goal was to explore their emotional experiences and the factors that influenced them over three years while teaching in rural primary schools. The research data was collected primarily through semi-structured interviews, teaching diaries, and narrative frameworks. Three-step coding and topic analysis were used to analyze the collected data. The data analysis revealed that the two novice teachers generated 62 emotions while interacting with various ecosystems. In Microsystems, teacher-student interaction has a strong influence on participants' emotions. Two participants experienced 19 positive emotions and 9 negative emotions during their interactions with the students. In addition, novice teachers may experience negative emotions if they are burdened with too many non-teaching tasks. In this study, two participants were able to effectively manage their negative emotions. The general emotional trend was positive, which motivated them to stay and continue teaching in the rural area. The results of this study have implications for the professional development of rural teachers and novice teachers.